The Use Of Telemedicine In The Digital Transformation Of Healthcare Services: A Literature Review - Abdul Haris Pontoh; Fariz Maulana; Marina Marina; Misbahudin Misbahudin; Sahpur Sahpur; Abdul Kadri (CV. AFDIFAL MAJU BERKAH, 2026)
Digital transformation in healthcare services has encouraged the use of technology to improve access, quality, and efficiency of healthcare delivery. One of the key innovations in this transformation is telemedicine, which enables healthcare services to be delivered remotely. This study aims to examine the utilization of telemedicine in the digital transformation of healthcare services through a systematic review approach. The method used was a systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Literature searches were conducted in PubMed, Scopus, ScienceDirect, Semantic Scholar, and Google Scholar within the publication years 2020–2025. The article selection process followed identification, screening, eligibility, and inclusion stages. A total of 13 articles that met the inclusion criteria were analyzed narratively. The results indicate that telemedicine improves access to healthcare services, supports health data integration, enhances patient engagement, and promotes more proactive and preventive care. Additionally, telemedicine contributes to improving the efficiency of healthcare systems. However, its implementation still faces challenges such as limited infrastructure, digital literacy, and issues related to data security and system integration. Therefore, telemedicine is an important strategy in the digital transformation of healthcare services that requires support from policies and technological system strengthening.